A case of premature ovarian insufficiency in Nijmegen breakage syndrome patient and review of literature. From gene mutation to clinical management. (2nd November 2019) - Szeliga, Anna; Zysnarska, Aleksandra; Szklarska, Zuzanna; Truszkowska, Ewelina; Podfigurna, Agnieszka; Czyzyk, Adam; Genazzani, Andrea R.; Chrzanowska, Krystyna; Meczekalski, Blazej
Abstract: Background: Nijmegen breakage syndrome (NBS) is an autosomal recessive disorder leading to chromosomal instability and an array of symptoms, including characteristic facial features (bird-like face), predisposition to malignancies, as well as hypergonadotropic hypogonadism. This case report discusses the diagnostic process and management of a 23-year-old Polish female patient who was admitted to hospital with symptoms of secondary amenorrhea and clinical features corresponding to NBS. Methods: Clinical examination, per-rectal ultrasound, laboratory diagnostics (including serum concentrations of FSH, LH, estradiol, testosterone, and TSH), as well as SSCP analysis and classic karyotyping were performed. Results: During hormonal evaluation elevated serum concentration of FSH and LH and decreased serum concentration of estradiol were measured. The genetic testing revealed translocation 7;14 (t(7;14)) and inversion 7 in 22% of examined cells which confirmed the initial hypothesis of NBS. The diagnosis was finally verified by identifying a Slavic founder mutation, c.657_661del5, on both allels of the NBN gene. Furthermore, hormonal serum evaluation conducted after four weeks allowed the patient to be diagnosed with premature ovarian insufficiency (POI) suspected earlier on the grounds of preliminary examinations (ultrasound imaging and laboratory tests). Conclusions: Chromosomal instability resulting from a mutation present in Nijmegen breakage syndrome patients might be a causative factor of premature ovarian insufficiency. Therefore, females diagnosed with NBS should undergo additional diagnostic procedures in order to determine further management and treatment.